Inflammatory leiomyosarcoma shows frequent co-expression of smooth and skeletal muscle markers supporting a primitive myogenic phenotype: a report of 9 cases with a proposal for reclassification as low-grade inflammatory myogenic tumor - Michal, Michael; Rubin, Brian P; Kazakov, Dmitry V; Michalová, Květoslava; Šteiner, Petr; Grossmann, Petr; Hájková, Veronika; Martínek, Petr; Švajdler, Marian; Agaimy, Abbas; Hadravský, Ladislav; Kalmykova, Antonina V; et al. (Virchows Archiv, 2020)
Inflammatory leiomyosarcoma (ILMS) is a very rare soft tissue tumor that usually follows an indolent clinical course, but long-term follow-up studies are lacking. Recent publications primarily focused on its genetic profile characterized by a near haploid genome. One study also showed these tumors to have upregulation of genes known to be crucial for skeletal muscle differentiation. Nevertheless, immunohistochemical expression of skeletal muscle markers, as well as markers that would help to distinguish ILMS from a long list of relevant differential diagnostic entities, has not been extensively studied. Nine cases of ILMS were collected and stained by a broad IHC panel which, besides others, contained MyoD1, myogenin, and PAX-7. A subset of cases was also analyzed by 2 different NGS assays and by MDM2 fluorescence in situ hybridization. Five male and 4 female patients ranged in age from 25 to 54 years (mean, 36 years). The tumors showed a predilection for intramuscular sites of the lower limbs (n = 4) and back (n = 2), whereas the remaining 3 cases affected an unspecified skeletal muscle, lung, and omentum. Follow-up with an average length of 10.6 years (range 0.5-22) was available for 8 patients. The omental tumor spread locally within the abdominal cavity, but the patient has been free of disease 7 years after treatment. None of the 5 patients with somatic soft tissue tumors (and follow-up longer than 1.5 years) had either recurrence or metastasis. Immunohistochemical studies revealed a substantial expression of skeletal muscle markers in almost all cases. This phenotype coupled with a highly characteristic genotype and significantly more indolent clinical behavior as compared with conventional leiomyosarcoma of deep soft tissue offers a strong rationale to change the current nomenclature. Based on the clinicopathological features and gene expression profile, we propose the name low-grade inflammatory myogenic tumor.
Keywords: Neoplasm Recurrence, Local; Leiomyosarcoma; Soft Tissue Neoplasms; MyoD1; Rhabdomyosarcoma; Humans; diferenciální diagnóza; Histiocyte-rich rhabdomyoblastic tumor; lidé středního věku; Biomarkers, Tumor; Immunoenzyme Techniques; Female; dospělí; Inflammation; Phenotype; Diagnosis, Differential; lidé; zánět; nádory měkkých tkání; nádorové biomarkery; Adult; imunoenzymatické techniky; kosterní svaly; ženské pohlaví; Male; Low-grade inflammatory myogenic tumor; Middle Aged; fenotyp; Muscle, Skeletal; lokální recidiva nádoru; Smooth muscle tumors; mužské pohlaví; Inflammatory leiomyosarcoma; leiomyosarkom